Principles of nano-optics - Novotny, Lukas (Cambridge University Press, 2006)
A comprehensive and broad overview of the theoretical concepts and experimental methods of nano-optics. This is the first textbook on the subject, covering nanoscale optical phenomena across many areas. Written for graduates who want to enter the field, it includes problem sets to reinforce and extend the discussion.
Keywords: Nanostructured materials.; Near-field microscopy.; Quantum optics.; Photonics.; elektronické knihy; electronic books